2013
DOI: 10.9734/bmrj/2013/4653
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Plasmid-Mediated ampC Genes in Clinical Isolates of Enterobacteriaceae from Cairo, Egypt

Abstract: Aims: To determine the prevalence of acquired pAmpCs in clinically important and relevant enterobacterial species and to characterize the molecular types of pAmpC present in our geographic area. Methodology: Sixty Enterobacterial clinical isolates resistant to third generation cephalosporins and to cephamycins were included in the study. Samples were collected for a period of 6 months between July 2008 and December 2008 from Theodor Bilharz Research Institute (TBRI), Egypt. Bacterial species were identified us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
2
12
1
Order By: Relevance
“…These results were in agreement with two studies carried in Cairo, Egypt, by Fam et al [17] and Hosny and Kashif [40] in which CMY was detected in 76.5% and 60% while DHA-1 in the 23.5% and 40%, respectively. On the other hand, in studies carried by Barwa et al [41] and Wassef et al [42], the FOX family showed the highest prevalence rate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were in agreement with two studies carried in Cairo, Egypt, by Fam et al [17] and Hosny and Kashif [40] in which CMY was detected in 76.5% and 60% while DHA-1 in the 23.5% and 40%, respectively. On the other hand, in studies carried by Barwa et al [41] and Wassef et al [42], the FOX family showed the highest prevalence rate.…”
Section: Discussionsupporting
confidence: 93%
“…These groups were suspected to originate from Hafnia alvei , Morganella morganii , Citrobacter freundii, Enterobacter cloaca, and Aeromonas spp. [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The resistance-associated genes bla TEM , bla SHV , and bla CMY were previously reported in Enterobacteriaceae isolated from septicaemic broilers [ 68 ] and from humans [ 69 , 70 ] in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…found by Akujobi et al (2012) and Fam et al (2013). The increased presence of plasmid mediated AmpC βlactamases worldwide is becoming of great concern (Jacoby, 2009).…”
Section: Discussionmentioning
confidence: 99%